Uncaria Gambir Roxb Business Development in the IM Kita Farmers Group in Boangmanalu Village, Salak District, Pakpak Bharat Regency - Siahaan, Sabda Dian Nurani; Siti Ulgari; Saronom Silaban; Dede Ruslan; Lenti Susanna Saragih; Dodi Pramana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Gambier plants thrive in tropical regions with sloping and hilly terrain, such as North Sumatra, West Sumatra, and Papua. The partners in this community service proposal are the Im Kita Farmers Group in Boangmanalu Village, Salak District, Pakpak Bharat Regency, who are gambier farmers. Over the past 7 years of running the business, the partners have faced many challenges, including the lack of digital marketing and the absence of a sharp business strategy management, resulting in weak business competitiveness. Addressing this issue urgently is necessary to improve the welfare of the partners and as a form of empowerment of our own natural resources. This community service activity has been carried out on July 27, 2024, and all stages from preparation to implementation have run smoothly. Through this activity, the partners have been trained in conducting digital marketing and business strategy management training.